A new species of Amphinemura from south China (Plecoptera: Nemouridae) - Yang, Ding; Li, Weihai; Sivec, Ignac (Zootaxa, 2005)
Amphinemura nanlingensis sp. nov. is described from Guangdong, China. Its relationship with related species of Amphinemura is discussed.